Infantile Intraoral Myofibroma of the Gum in A 2-Year-Old Child - Igaz, Martin; Kopáni, Martin; Biró, Csaba (Annals of Pathology and Laboratory Medicine, 2018)
Intraoral myofibroma is a rare tumor. It occurs most frequently in childhood, in particular between the ages of 2 and 9, mostly intraosseally in the mandibula, tongue, oral mucosa and less frequently in the gum. Clinical assessment of the lesion due to rapid growth may imitate malignancy. Histomorphologically, the myofibroma is mostly a benign lesion with excellent prognosis. A sufficient surgical excision is a sufficient therapy. The most common alternatives in the differential diagnostics include fibrous epulis, pyogenic granuloma, peripheral odontogenic fibroma, nodular fasciitis, fibroma of tendon sheaths, leiomyoma, dermatomyofibroma, myoepricytoma, glomangiopericytoma, angioleiomyoma. Results of genetic examinations reveal a vascular disease with impairment of pericytes or their progenitors that are connected with point mutations of 5q32 gene. In our case, we present an examination for consultation on an intraosseous tumor in a 2-year-old boy with minimum clinical history, accessible perioperative local finding of the 4x3 cm tumor in the mandibular area with usuration of the bone, with only several torn, greyish to white pieces sent for examination.